Effectiveness of forward freight agreements in mitigating capesize ship-owners' business risk between 2009 and 2014 - Wang, Wenhao (2016)
Shipowners have employed various risk management tools to reduce their exposure in the inherently risky freight market to ensure survival. Traditionally, they utilize physical hedging tools such as Time Charters (TC) to hedge their earnings. The advent of Forward Freight Agreements (FFA), a paper hedge, provide shipowners with an alternative tool to reduce their risk through the financial market. This paper aims to investigate which hedging tool is more effective in helping shipowners mitigate their business risk. This paper first discussed extensively on the risk management of the shipowner and how being able to forecast the future freight market will facilitate the process. This paper then adopted a statistical approach and analyzed the correlation between the FFA price and its respective final settlement price. Using data from the published data from The Baltic Exchange and Bloomberg, an ordinary least-square model was adopted to determine the strength of the correlation as well as the statistical significance of the regression. Each forward contract period that has a strong correlation and is statistically significant will be accurate in predicting future prices up to that respective period. Overall, it was found that none of the contract periods is accurate in predicting future prices given the set criteria. Future studies may involve selecting a most suitable model such as a time series model or variables to test for the accuracy in forecasting future prices.